Thomas Aquinas on virtue and human flourishing - Theron, Stephen, 1939- (Cambridge Scholars Publishing, 2018)
Thomas Aquinas offers teleological systematisation of the habits needed for human flourishing. His metaphysical jurisprudence remodels ethics upon this, rather than on a moral precept. ""Eternal law"" governing the world determines ""natural law"", reflected in human legislation (a variety of the ""anthropic principle""). Finally, law, unwritten, is infused spirit as self-consciousness, ""universal of universals"". Acquired virtues elicit this, become effusion, represented in religion as gifts or graces. But mind's or spirit's omnipresence, necessarily ""closer to me than I am to myself"", sup